INTEGRATED RECLAMATION IMPROVED ON THE DEVELOPMENT OF INSULATED LANDS, TAKING INTO ACCOUNT SOIL CONSERVATION AGRICULTURE OF THE NAMANGAN ADYRS - Dadakhodzhaev Anvarzhon; Mamadzhanov Maruf Mahmudzhanovich; Khaydarov Sherzod Ergashalievich (Galaxy International Interdisciplinary Research Journal, 2023)
The development of the ravine areas, taking into account the soil-protected agriculture of the Namangan adyrs, on the planned surface of the ravine area, new subtypes of technogenic soils are formed, represented by outcrops and embankments. As well as a comprehensive radical reclamation of ravine lands. We studied the totality of the agro-forest, reclamation, and hydro-reclamation measures for the radical reclamation of the ravine lands of the valley.